Longitudinal Analysis of the Utility of Liver Biochemistry as Prognostic Markers in Hospitalized Patients With Corona Virus Disease 2019. Issue 9 (10th July 2021) - Wang, Tingyan; Smith, David A.; Campbell, Cori; Harris, Steve; Salih, Hizni; Várnai, Kinga A.; Woods, Kerrie; Noble, Theresa; Freeman, Oliver; Moysova, Zuzana; Marjot, Thomas; Webb, Gwilym J.; et al.
Abstract : The association of liver biochemistry with clinical outcomes of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is currently unclear, and the utility of longitudinally measured liver biochemistry as prognostic markers for mortality is unknown. We aimed to determine whether abnormal liver biochemistry, assessed at baseline and at repeat measures over time, was associated with death in hospitalized patients with COVID‐19 compared to those without COVID‐19, in a United Kingdom population. We extracted routinely collected clinical data from a large teaching hospital in the United Kingdom, matching 585 hospitalized patients who were SARS‐CoV‐2 real‐time reverse transcription‐polymerase chain reaction (RT‐PCR) positive to 1, 165 hospitalized patients who were RT‐PCR negative for age, sex, ethnicity, and preexisting comorbidities. A total of 26.8% (157/585) of patients with COVID‐19 died compared to 11.9% (139/1, 165) in the group without COVID‐19 ( P  < 0.001). At presentation, a significantly higher proportion of the group with COVID‐19 had elevated alanine aminotransferase (20.7% vs. 14.6%, P  = 0.004) and hypoalbuminemia (58.7% vs. 35.0%, P  < 0.001) compared to the group without COVID‐19. Within the group with COVID‐19, those with hypoalbuminemia at presentation had 1.83‐fold increased hazards of death compared to those with normal albumin (adjusted hazard ratio [HR], 1.83; 95% confidence interval [CI], 1.25‐2.67), while the hazard of death was ~4‐fold higher in those aged ≥75 years (adjusted HR, 3.96; 95% CI, 2.59‐6.04) and ~3‐fold higher in those with preexisting liver disease (adjusted HR, 3.37; 95% CI, 1.58‐7.16). In the group with COVID‐19, alkaline phosphatase (ALP) increased (R = 0.192, P  < 0.0001) and albumin declined (R = −0.123, P  = 0.0004) over time in patients who died. Conclusion: In this United Kingdom population, liver biochemistry is commonly deranged in patients with COVID‐19. Baseline hypoalbuminemia and rising ALP over time could be prognostic markers for death, but investigation of larger cohorts is required to develop a better understanding of the relationship between liver biochemistry and disease outcome.